Molecular detection and characterization of Bartonella spp. in small mammals in the Amazonia and Cerrado biomes, midwestern Brazil - Pacheco, Thábata dos Anjos; Amaral, Renan Bressianini do [UNESP]; Ikeda, Priscila [UNESP]; Maia, Maerle Oliveira; Lee, Daniel Antônio Braga [UNESP]; Semedo, Thiago Borges Fernandes; de Mendonça, Ravena Fernanda Braga; Pedroni, Fernando; Horta, Maurício Claudio; Rossi, Rogério Vieira; André, Marcos Rogério [UNESP]; Pacheco, Richard de Campos (Elsevier, 2024)
Although Bartonella spp. have been worldwide described in rodents and bats, few studies have reported these agents in marsupials. The present work aimed to investigate the occurrence and genetic diversity of Bartonella in small mammals (rodents, marsupials, and bats) and associated ectoparasites in two ecoregions (Amazonia and Cerrado biomes) in midwestern Brazil. For this purpose, DNA samples from 378 specimens of small mammals (128 rodents, 111 marsupials, and 139 bats) and 41 fleas (Siphonaptera) were screened for the Bartonella genus employing a quantitative real-time PCR assay (qPCR) based on the nuoG (nicotinamide adenine dinucleotide dehydrogenase gamma subunit) gene. Then, positive samples in qPCR were submitted to conventional PCR (cPCR) assays targeting the gltA, ftsZ, and rpoB genes. One (0.78 %) rodent, 23 (16.54 %) bats, and 3 (7.31 %) fleas showed positive results in the qPCR for Bartonella sp. After cPCR amplification and sequencing, 13 partial Bartonella DNA sequences of the following genes were obtained only from bats´ blood samples: 9 gltA (citrate synthase), 3 ftsZ (cell division protein), and 1 rpoB (RNA polymerase beta subunit). The maximum likelihood inference based on the gltA gene positioned the obtained sequences in three different clades, closely related to Bartonella genotypes previously detected in other bat species and bat flies sampled in Brazil and other countries from Latin America. Similarly, the ftsZ sequences clustered in two different clades with sequences described in bats from Brazil, other countries from Latin America, and Georgia (eastern Europe). Finally, the Bartonella rpoB from a specimen of Lophostoma silvicolum clustered with a Bartonella sp. sequence obtained from a Noctilio albiventris (KP715475) from French Guiana. The present study provided valuable insights into the diversity of Bartonella genotypes infecting bats from two ecoregions (Amazonia and Cerrado) in midwestern Brazil and emphasized that further studies should be conducted regarding the description and evaluation of different lineages of Bartonella in wild small mammals and their ectoparasites in different Brazilian biomes.
Keywords: Bartonellosis; Chiropteran; Fleas; Marsupials; Phylogeny; qPCR; Rodents